Recent Advances in Metal–Organic Framework-Based Nanozymes for Intelligent Microbial Biosensing: A Comprehensive Review of Biomedical and Environmental Applications - Alemayehu Kidanemariam; Sungbo Cho (Biosensors)
Metal–organic framework (MOF)-based nanozymes represent a groundbreaking frontier in advanced microbial biosensing, offering unparalleled catalytic precision and structural tunability to mimic natural enzymes with superior stability and specificity. By engineering the structural features and forming composites, MOFs are precisely tailored to amplify nanozymatic activity, enabling the highly sensitive, rapid, and cost-effective detection of a broad spectrum of microbial pathogens critical to biomedical diagnostics and environmental monitoring. These advanced biosensors surpass traditional enzyme systems in robustness and reusability, integrating seamlessly with smart diagnostic platforms for real-time, on-site microbial identification. This review highlights cutting-edge developments in MOF nanozyme design, composite engineering, and signal transduction integration while addressing pivotal challenges such as biocompatibility, complex matrix interference, and scalable manufacturing. Looking ahead, the convergence of multifunctional MOF nanozymes with portable technologies and optimized in vivo performance will drive transformative breakthroughs in early disease detection, antimicrobial resistance surveillance, and environmental pathogen control, establishing a new paradigm in next-generation smart biosensing.